2014
DOI: 10.1007/s12264-013-1430-z
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase E (NF-α1): a new trophic factor in neuroprotection

Abstract: Carboxypeptidase E (CPE) is a prohormone-processing enzyme and sorting receptor that functions intracellularly. However, recent studies have demonstrated that CPE acts as a trophic factor extracellularly to up-regulate the expression of a pro-survival gene. This mini-review summarizes the roles of CPE in neuroprotection and the implications for neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 32 publications
(41 reference statements)
0
30
0
Order By: Relevance
“…Sortilin, which is an important intracellular sorting receptor, plays a role in targeting some neurotrophins to the regulated secretory vesicles via interaction with a specific sequence of the pro-domain of neurotrophins 15-17. In addition, to sequence information in the pro-region of neurotrophins, the mature neurotrophin has a sequence signal that is recognized by the sorting receptor carboxypeptidase E (CPE) and results in targeting the neurotrophins to the regulated pathway of secretion 18,19. Finally, the importance of these sorting motifs in targeting neurotrophins to the secretory vesicles has been confirmed by experiments, which showed that swapping of these motifs between different neurotrophins might alter the sorting of neurotrophins to either of the secretory pathways 9…”
Section: General Conceptmentioning
confidence: 99%
“…Sortilin, which is an important intracellular sorting receptor, plays a role in targeting some neurotrophins to the regulated secretory vesicles via interaction with a specific sequence of the pro-domain of neurotrophins 15-17. In addition, to sequence information in the pro-region of neurotrophins, the mature neurotrophin has a sequence signal that is recognized by the sorting receptor carboxypeptidase E (CPE) and results in targeting the neurotrophins to the regulated pathway of secretion 18,19. Finally, the importance of these sorting motifs in targeting neurotrophins to the secretory vesicles has been confirmed by experiments, which showed that swapping of these motifs between different neurotrophins might alter the sorting of neurotrophins to either of the secretory pathways 9…”
Section: General Conceptmentioning
confidence: 99%
“…Since CPE has been shown to be a survival and neuroprotective factor[10,11,20], we tested whether the T to C mutation at 980 sitein CPE gene would affect these properties. We first analyzed the transcript expression of WT-CPE and TC-CPE.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a person who bears homozygosity for a truncating mutation of the CPE gene displayed intellectual disability[19]. The hypothesis that CPE mutation would contribute to neurological disorders is also supported by the animal studies showing that CPE-KO mice had the neuronal loss of the CA3 region of hippocampus, displayed memory deficits and depressive-like behaviors[12,13,20]. …”
Section: Discussionmentioning
confidence: 99%
“…17,8 CPE has also been implicated in cancer progression [18][19][20][21] and as a neuro-trophic factor regulating brain functions. [22][23][24][25][26] Lately, it was found that CPE is also involved in other biological processes such as bone homeostasis 27 and bowel disease. 28 We have previously shown that CPE negatively regulates the oncogenic canonical Wnt signaling pathway by interacting with Wnt3a leading to decreased β-catenin protein levels and reduced Wnt signaling levels.…”
Section: Discussionmentioning
confidence: 99%